(untitled) (Journal of Music Research Online, 2025)
Sweet Alcaic Metres is an audiovisual work commissioned by Create NSW to contribute to the Regional Futures project in 2023. The creators were asked to respond to the prompt ’What does the future look like in your region?’ and were encouraged to engage with experts and members of the community to develop a creative response. This audiovisual project began by exploring historical creative responses to changes in the environment through the writings and poetry of Judith Wright, followed by discussions with soil scientists, engineers, and station owners to capture the use, misuse and underuse of natural and civic resources within the New England North West area of New South Wales. This project is an example of qualitative arts-based research combining both arts-informed and arts-informing inquiries as a representation and response to an issue or situation.